Contribution of Trunk Muscles to Upright Sitting with Segmental Support in Children with Spinal Cord Injury - Goutam Singh; Sevda Aslan; Beatrice Ugiliweneza; Andrea Behrman (MDPI AG, 2020)
To investigate and compare trunk control and muscle activation during uncompensated sitting in children with and without spinal cord injury (SCI). Static sitting trunk control in ten typically developing (TD) children (5 females, 5 males, mean (SD) age of 6 (2)y) and 26 children with SCI (9 females, 17 males, 5(2)y) was assessed and compared using the Segmental Assessment of Trunk Control (SATCo) test while recording surface electromyography (EMG) from trunk muscles. The SCI group scored significantly lower on the SATCo compared to the TD group. The SCI group produced significantly higher thoracic-paraspinal activation at the lower-ribs, and, below-ribs support levels, and rectus-abdominus activation at below-ribs, pelvis, and no-support levels than the TD group. The SCI group produced significantly higher lumbar-paraspinal activation at inferior-scapula and no-support levels. Children with SCI demonstrated impaired trunk control with the ability to activate trunk muscles above and below the injury level.